The growth and probiotic characteristics of Bacillus velezensis BS in soybean meal used as synbiotic-like preparations for Litopenaeus vannamei culture - Hoang, Phuong Ha; Nguyen, Minh Thi; Chu, Nhat Huy; Bui, Huong Giang (Vietnam Journal of Biotechnology, 2023)
Soybean meal (SBM) is the by-product of soybean oil extraction. It is well known to contain at least 47% protein and more than 6% crude fiber. This study showed that Bacillus velezensis BS grew well in medium containing 1% SBM and gained the prebiotic index and activity score of 15.40 ± 4.10 and 0.85 ± 0.22, respectively. In this medium, B. velezensis BS showed various probiotic characteristics, such as digestive enzyme secretion (α-amylase, cellulase, and protease), anti-Vibrio parahaemolyticus, biofilm formation on the solid surface after 24 h of interaction and the ability to grow in a broad range of environmental conditions (pH 6-9, temperature of 20-45ºC, salinity of 4%). In addition, SBM fermented with B. velezensis BS significantly reduced 79.7 ± 1.9% of the trypsin inhibitor content. Dietary supplement of the fermented product in Litopenaeus vannamei culture improved the specific growth rate of shrimp by approximately 7 times and concomitantly decreased the density of V. parahaemolitycus pathogen by 10 times compared to the group without synbiotic-like fed. Hence, the B. velezensis BS and its SBM fermented product were suggested as a potential feed additive in aquaculture applications.